The Correlation Between Self-directed Learning Readiness (SDLR) and Academic Procrastination in Medical Students of Medicine Faculty Sebelas Maret University - Faizah, Sheila Rahmi Ismi; Pamungkasari, Eti Poncorini; Randita, Amandha Boy Timor (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction : Self-directed learning readiness (SDLR) is a personâs readiness to study autonomically. The components of SDLR are self management, self control and academic motivation. These three components are usually correlated negatively with academic procrastination and feared to be a negative impact on learning. This research was aimed to find out the correlation between SDLR and academic procrastination in Medical Students of Medicine Faculty at Sebelas Maret University. Methods: This research was an analytical observation with cross sectional method. Sample of this research were all medical students of Medicine Faculty Sebelas Maret University. SDLR and academic procrastination were measured by questionnaire. The data were analyzed with Pearson correlation and linear regression. Results: Results of Pearson correlation were r = -0,37 and p = 0,000. Results of linear regression were one SDLR score would reduce as much as 0,23 academic procrastination score (p = 0,000) and the increase of age would elevate as much as 2,1 academic procrastination score (p = 0,031). Conclusion: There was a significant negative correlation between SDLR and academic procrastination in medical students of Medicine Faculty Sebelas Maret University. The strength of the correlation was low. One SDLR score would reduce as much as 0,23 academic procrastination score and the increase of age would elevate as much as 2,1 academic procrastination score. KeywordsÂ Â Â Â : self-directed learning readiness (SDLR), academic procrastination, medical students.